Notes on unrest among Moroccan youth: Migrant projects and internal mobility in Morocco as a prelude to international migration - Capote, Alberto (Documents d'Anàlisi Geogràfica, 2014)
The migratory journey of Moroccan immigrants in Spain during the past decade began, very often, before crossing the border. In many cases it was just this first migration experience in Morocco which was the factor that finally triggered the decision to migrate abroad, and it was also the expression of the unease of Moroccan youth in the face of the opportunities being offered by society. In this paper we analyze the starting points of migratory projects from a sample of young Moroccan immigrants in Andalusia, with particular emphasis on those cases where close links between migration abroad and internal migration in Morocco have been detected. For this we employ empirical research conducted in five municipalities of the Andalusian provinces of Cordoba and Granada.